Analysis of FUS-CHOP fusion transcripts in different types of soft tissue liposarcoma and their diagnostic implications - Willeke, Frank; Ridder, Rüdiger; Mechtersheimer, Gunhild; Schwarzbach, Matthias; Duwe, Alexander; Weitz, Jürgen; Lehnert, Thomas; Herfarth, Christian; Knebel Doeberitz, Magnus von (Clinical cancer research, 1998)
In myxoid and round cell liposarcomas, a specific chromosomal translocation [(12;16)(q13;p11)] results in the expression of chimeric fusion transcripts encompassing parts of the FUS gene (16p11) at their 5' ends and the CHOP gene (12q13) at their 3' ends. Using a reverse transcription-PCR protocol, we determined the prevalence of FUS-CHOP fusion transcripts in a series of liposarcoma samples. Fusion transcripts were detected in 13 of 30 biopsy samples from soft tissue liposarcomas. Expression of fusion transcripts was not restricted to myxoid and round cell liposarcomas, as suggested previously; it was also detected in 1 of 3 well-differentiated and 4 of 14 pleomorphic liposarcomas. Sequence analysis revealed four different FUS-CHOP fusion transcript variants, two of which have not been described before. Furthermore, using FUS-CHOP fusion transcripts as targets in reverse transcription-PCR assays, we detected disseminated tumor cells in peripheral blood or bone marrow in 3 of 5 patients undergoing surgery for soft tissue liposarcoma.